The Pay Gap: Pay Inequality but Pay Equity Found in the Construction Industry - Beyer, Richard; Hensersky, Travis; Thomas, Adrian (Journal of Organizational Psychology, 2019)
Pay inequality was found for Project Managers (N=317) in an organization with a history of high pay satisfaction and that has been deemed a “best place to work.” Women made 87 cents on the male dollar. However, Hayes conditional process modeling found that when productivity-relevant inputs (company experience, previous experience, performance ratings, education) were included there were neither direct effects of gender on pay nor were there indirect effects of gender on company experience–pay, previous experience–pay, performance rating–pay or education–pay relationships. Implications include support for the notion that equality and equity may not be synonymous.